Procedural knowledge in under-14 category volleyball players - Claver, F.; Fernández-Echeverría C.; Gil, A.; Moreno, A.; Moreno, M. P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The main aim of this study was to analyze the procedural knowledge (PK) of the 306 players (M: 13.61; SD: .796), from de Spanish Championship in Under-14 category depending on de federated experience and performance. The dependent variable was procedural knowledge (“know how”) measured trough the Procedural Knowledge Questionnaire (Alberto Moreno et al., 2013). The independent variables were experience in federated practice and performance. Results showed statistical differences in procedural knowledge due to experience and performance. In addition, were also found the relationships between procedural knowledge, experience and performance. These results agree with previous studies that highlighted the importance of these variables into the road to the sport excellence. It is necessary for trainers to take these variables in order to propose specifically training tasks to optimize players’ formative process.